Long Non-coding RNAs in Human Disease - Morris, Kevin V. (Current topics in microbiology and immunology, 2016)
Understanding the Complex Circuitry of lncRNAs at the X-inactivation Center and its Implications in Disease Conditions -- Long Non-coding RNA ANRIL and Polycomb in Human Cancers and Cardiovascular Disease -- Form and function of exosome associated long non-coding RNAs in cancer -- Long Non-coding RNAs in Lung Cancer -- Pseudogene-expressed RNAs: Emerging roles in gene regulation and disease -- Functional long non-coding RNAs in vascular smooth muscle cells -- Long Non-coding RNAs as Targets and Regulators of Nuclear Hormone Receptors -- Non-coding transcriptional landscape in human aging -- LncRNAs in stress response -- Expression Specificity of Disease-Associated lncRNAs: towards Personalized Medicine